Ixodes scapularis Tick Parasitizing Dog in Dawson County, Montana, USA, 2023 - Philip E. Stewart; Justin B. Lack; Marni Rolston; Kimmo Virtaneva; Paul A. Beare; Craig M. Martens; Marshall E. Bloom; Tom G. Schwan (Emerging Infectious Diseases)
In October 2023, a partially engorged female Ixodes tick was removed from a dog in Bozeman, Montana, USA, that had recently spent time in eastern Montana. The tick was identified as I. scapularis according to morphologic characteristics and genomic sequencing, suggesting an expanded geographic distribution requiring continued public health surveillance.